2022
DOI: 10.3390/ijms232012366
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Flagellin Activates the Intracellular NLRC4 Inflammasome

Abstract: Clostridioides difficile (C. difficile), is a major cause of nosocomial diarrhea and colitis. C. difficile flagellin FliC contributes toxins to gut inflammation by interacting with the immune Toll-like receptor 5 (TLR5) to activate nuclear factor-kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) signaling pathways. Flagella of intracellular pathogens can activate the NLR family CARD domain-containing protein 4 (NLRC4) inflammasome pathway. In this study, we assessed whether flagellin of the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…We anticipated that shear stress would only prime the NLRP3 inflammasome for activation and would not affect the priming of the NLRP1 and AIM2 inflammasomes since previous studies suggested that shear stress would not prime these inflammasomes. , While NF-kB is involved in the priming of the NLRC4 inflammasome pathway, Gram-negative bacteria are required to initiate activation; so, even if shear stress could prime this pathway for activation, the NLRC4 inflammasome could not become activated. To confirm this, we separately primed NLRP3 KO and caspase-1 KO iBMDMs with 3 magnitudes of shear stress for 30 min, followed by 1 h nigericin treatment before imaging via confocal microscopy (Figure A,B). Similar to the WT iBMDMs used in this study, the KO iBMDMs were engineered to express a CFP tag on the ASC adaptor protein.…”
Section: Resultsmentioning
confidence: 97%
“…We anticipated that shear stress would only prime the NLRP3 inflammasome for activation and would not affect the priming of the NLRP1 and AIM2 inflammasomes since previous studies suggested that shear stress would not prime these inflammasomes. , While NF-kB is involved in the priming of the NLRC4 inflammasome pathway, Gram-negative bacteria are required to initiate activation; so, even if shear stress could prime this pathway for activation, the NLRC4 inflammasome could not become activated. To confirm this, we separately primed NLRP3 KO and caspase-1 KO iBMDMs with 3 magnitudes of shear stress for 30 min, followed by 1 h nigericin treatment before imaging via confocal microscopy (Figure A,B). Similar to the WT iBMDMs used in this study, the KO iBMDMs were engineered to express a CFP tag on the ASC adaptor protein.…”
Section: Resultsmentioning
confidence: 97%
“…This was demonstrated by confocal microscopy with the observation of the internalization of FliC tagged with a green fluorescent protein (GFP) into the intestinal Caco-2/TC7 cell line. Further, the activation of NLRC4, the cleavage of pro-caspase-1 into two subunits, p20 and p10, and also the cleavage of gasdermin D, were shown, suggesting that the caspase-1 and NLRC4 inflammasome activation by FliC contributes to the inflammatory process of C. difficile infection [53].…”
Section: Acting As Immunomodulators By Triggering Proinflammatory Cyt...mentioning
confidence: 94%
“…Additionally, bacterial EVs containing flagellin can induce pyroptosis in macrophages by activating the NLRC4 inflammasome rather than the NLRP3 inflammasome ( Bitto et al., 2018 ). Unlike the NLRP3 inflammasome, the NLRC4 inflammasome specifically recognizes bacterial flagellin and flagellin-like molecules, leading to a more specific and rapid activation ( Gram et al., 2021 ; Chebly et al., 2022 ). For example, Salmonella EVs containing flagellin can quickly activate the NLRC4 inflammasome in a shorter time compared to flagellin-deficient E. coli and Salmonella EVs ( Yang et al., 2020 ).…”
Section: The Impact Of Bacterial Evs On Macrophage Immune Functionmentioning
confidence: 99%